UPLC-Q-TOF-MS/MS Analysis of Seco-Sativene Sesquiterpenoids to Detect New and Bioactive Analogues From Plant Pathogen Bipolaris sorokiniana - Wang, Yan-Duo; Yang, Jian; Li, Qi; Li, Yuan-Yuan; Tan, Xiang-Mei; Yao, Si-Yang; Niu, Shu-Bin; Deng, Hui; Guo, Lan-Ping; Ding, Gang (Frontiers in Microbiology, 2022)
Seco-sativene sesquiterpenoids are an important member of phytotoxins, and plant-growth regulators isolated from a narrow spectrum of fungi. In this report, eight seco-sativene sesquiterpenoids (1-8) were first analyzed using UPLC-Q-TOF-MS/MS technique in positive mode, from which their mass fragmentation pathways were suggested. McLafferty rearrangement, 1,3-rearrangement, and neutral losses were considered to be the main fragmentation patterns for the [M+1]+ ions of 1-8. According to their structural features (of different substitutes at C-1, C-2 and C-13) in compounds 1-8, five sub-types (A-E) of seco-sativenes were suggested, from which sub-types A, B/D and E possessed the diagnostic daughter ions at m/z 175, 189, and 203, respectively, whereas sub-type C had the characteristic daughter ion at m/z 187 in the UPLC-Q-TOF-MS/MS profiles. Based on the fragmentation patterns of 1-8, several known compounds (1-8) and two new analogues (9 and 10) were detected in the extract of plant pathogen fungus Bipolaris sorokiniana based on UPLC-Q-TOF-MS/MS analysis, of which 1, 2, 9 and 10 were then isolated and elucidated by NMR spectra. The UPLC-Q-TOF-MS/MS of these two new compounds (9 and 10) were consistent with the fragmentation mechanisms of 1-8. Compound 1 displayed moderate antioxidant activities with IC50 = 0.90 mM and IC50 = 1.97 mM for DPPH and ABTS+• scavenging capacity, respectively. The results demonstrated that seco-sativene sesquiterpenoids with the same sub-types possessed the same diagnostic daughter ions in the UPLC-Q-TOF-MS/MS profiles, which could contribute to structural characterization of sativene sesquiterpenoids. Our results also further supported that UPLC-Q-TOF-MS/MS is a powerful and sensitive tool for dereplication and detection of new analogues from crude extracts of different biological origins.